Identifikasi Informasi perguruan tinggi negeri dengan model knowledge management - Abu Anwar; Okfalisa Okfalisa; Elin Haerani (Sosial Budaya, 2013)
In theory and practice, knowledge management (knowledge management) is part of the strategy implementation process. Knowledge management is a systematic action to identify, document, and distribute all Solving). The involvement of administrative management knowledge, both top level, middle, or bottom becomes a very important thing. Well in detecting the problem, generating solutions, evaluating the decision to apply the knowledge that has been tested as a product and service in the implementation of strategy. This activity can be used to make the issues become clearer and under proper supervision. Despite the heavy dotted knowledge management to “technology“, in this case the role of “man“ needs to be taken into account in order to complete the process of knowledge management integrating various angles between technology, human strategies through four areas to view. However, the hypothesis of cause and effect of the method can be used as a basis for understanding knowledge management and implementation.